Integrated use of phosphate-solubilizing Bacillus subtilis strain IA6 and zinc-solubilizing Bacillus sp. strain IA16: a promising approach for improving cotton growth - Ahmad, Iqra; Ahmad, Maqshoof; Hussain, Azhar; Jamil, Moazzam (Folia microbiologica, 2021)
Mineral nutrition of crop plants is one of the major challenges faced by modern agriculture, particularly in arid and semi-arid regions. In alkaline calcareous soils, the availability of phosphorus and zinc is critically less due to their fixation and precipitation as complexes. Farmers use fertilizers to fulfill crop requirements, but their efficacy is less, which increases production costs. Plant growth-promoting rhizobacteria (PGPR) can improve the availability of crop nutrients through solubilizing the insoluble compounds of phosphorus and zinc in soil. In the present study, a total of 40 rhizobacterial isolates were isolated from cotton rhizosphere and screened for improving cotton growth through the solubilization of phosphorus and zinc. Out of these 40 isolates, seven isolates (IA2, IA3, IA6, IA7, IA8, IA13, and IA14) efficiently solubilized insoluble rock phosphate while seven isolates (IA10, IA16, IA20, IA23, IA24, IA28, and IA30) were more efficient in solubilizing insoluble zinc oxide. In liquid media, strain IA7 (2.75 μg/mL) solubilized the highest amount of phosphate while the highest concentration of soluble zinc was observed in the broth inoculated with strain IA20 (3.94 μg/mL). Seven phosphate-solubilizing and seven zinc-solubilizing strains were evaluated using jar trial to improve the growth of cotton seedlings, and the results were quite promising. All the inoculated treatments showed improvement in growth parameters in comparison with control. Best results were shown by the combined application of IA6 and IA16, followed by the combination of strains IA7 and IA20. Based on the jar trial, the selected isolates were further characterized by plant growth-promoting characters such as siderophores production, HCN production, ammonia production, and exopolysaccharides production. These strains were identified through 16S rRNA sequencing as Bacillus subtilis IA6 (accession # MN005922), Paenibacillus polymyxa IA7 (accession # MN005923), Bacillus sp. IA16 (accession # MN005924), and Bacillus aryabhattai IA20 (accession # MN005925). It is hence concluded that the integrated use of phosphate-solubilizing and zinc-solubilizing strains as potential inoculants can be a promising approach for improving cotton growth under semi-arid conditions.
Keywords: RNA ribozomální 16S; rhizosféra; Paenibacillus polymyxa; Bacillus; fosfáty; fosfor; očkovadla agrotechnická; Soil; zinek; Rhizosphere; Phosphorus; Agricultural Inoculants; RNA, Ribosomal, 16S; fylogeneze; Zinc; půdní mikrobiologie; Soil Microbiology; Phosphates; Gossypium; půda; Phylogeny